Three's a crowd! - O'Ryan, Ray (O'Ryan, Ray. Galaxy Zack, 2013)
"Zack is thrilled when his best friend on Earth, Bert Jones, visits for the weekend. But when Zack introduces Bert to Drake, his best friend on Nebulon, trouble begins!"--